Exploration of Industry Partner Support in the Implementation of Internships in the Independent Learning–Independent Campus Program - Amir Fatah; Hasyim As'ari (CV. Edutechnium Indonesia, 2025)
The independent learning campus policy (MBKM) by the Minister of Education and Culture of Indonesia has given a new nuance in implementing education in higher education. Students through MBKM are given the right to get hands-on experience in the field for a minimum of three semesters through eight activity programs, one of which is an internship in industry. Industrial internships are learning activities off campus or in the field that involve students, universities, and industry. Partner industries strongly influence the success of this internship program, as industrial internships in the MBKM program require students to study in partner industries for six months. The purpose of this study is to describe the support of industrial partners in the implementation of industrial internships and to describe the forms of industrial support in realizing student independence in learning. This research is a qualitative descriptive study. The research was conducted in 39 partner industries in the industrial internship program for students of the Automotive Engineering Faculty of Engineering, Yogyakarta State University, in 2020, spread throughout Indonesia. Data collection techniques are forum discussion groups (FGD) and documentation. The results show that at the MBKM internship planning stage, partner industries have been involved in mapping the number of students who can participate in the program, offering models of internship forms according to partner industry conditions, and evaluation models that allow optimizing the implementation of internships. At the internship implementation stage, the partner industry supports students conducting industrial practices in their field of interest. It will enable participants to analyze partner industry deficiencies, find solutions, and apply them directly to the field.